MARITIME CULTURE IMPLEMENTATION OF THE BAJAU SETTLEMENT – A CASE STUDY OF SAMA BAHARI VILLAGE, WAKATOBI ISLANDS - Nurul Istiqamah Ulil Albab (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2020)
The Bajau as a group of indigenous ‘sea nomad’ considered as the representatives of the maritime community, who have a unique way of dwelling, kept close to the shore by erecting houses on stilts. This research is to reveal the composition principles of the Bajau settlement with its unique “on the sea” environment in Sama Bahari village, Wakatobi Regency, Southeast Sulawesi province, and to correlate maritime culture to their dwelling for the local genius identification in a spatial context. Their habit regarding maritime was defined to the term of space, such as the existing facilities on the environment and their land plot to support seafaring activities. The structure of constructed house and infrastructure were built to support their way of moving and their need to survive in the condition of the maritime realm.